One single dose of rituximab added to a standard regimen of CHOP in primary treatment of follicular lymphoma appears to result in a high clearance rate from circulating bcl-2/IgH positive cells: Is the end of molecular monitoring near? - Schmitt, Christina; Grundt, Alexander; Buchholtz, Christian; Scheuer, Lars; Benner, Axel; Hensel, Manfred; Ho, Anthony Dick; Leo, Eugen (Leukemia research, 2006)
Accurate monitoring of the t(14;18) translocation is regarded as highly desirable in patients with follicular lymphoma (FL) as absence of bcl-2/IgH positive cells has been correlated with a reduced risk of recurrence and, more recently, pre-treatment t(14;18) load with response to rituximab (R; Blood 2004;103:4416-23). With the arrival of R clinical and molecular remission rates for various lymphoma entities improved significantly, creating the need to carefully review and reassess the role of PCR negativity for clinical outcome, specifically when considering the prolonged presence of the drug as compared to chemotherapy. To determine the rate of molecular clearance achieved by the addition of different doses of R 16 newly diagnosed, t(14;18) positive patients with FL (Ann Arbor stages III/IV) were investigated before, during and after primary chemotherapy with six cycles of CHOP combined with varying (1, 3 or 6) cycle numbers of R (varR1-, varR3- or varR6-CHOP, respectively) regarding molecular remission status. For this purpose classic nested PCR as well as a newly established RQ-PCR employing juxtaposed hybridisation probes were employed to assess molecular remission prior, during and post therapy. Interestingly, administering just a single cycle of R (varR1-CHOP) in combination with a standard regimen of CHOP resulted in rapid and effective clearance of t(14;18) carrying cells from the peripheral blood of 4/5 patients in this treatment group. 6/8 (6/8) varR1-/varR3-CHOP patients were fully cleared and 8/8 (7/8) var6-CHOP patients as assessed by RQ- (nested) PCR. This indicates the high clearance capacity of this combination therapy approach even when adding a very low cycle number of R (1 and 3, respectively) to CHOP in primary therapy of FL. In summary, the relationship established between molecular clearance and minimal residual disease/risk of recurrence may have to be redefined in the times of R. Upcoming large prospective trials will have to elucidate to what degree the clearance of peripheral blood from t(14;18) positive cells can still be regarded as informative regarding absence of minimal residual disease, remission status and/or risk of recurrence.
Available online: 10 March 2006
Gesehen am 05.11.2021